Smoking status and endothelial function in Japanese men - Hashimoto, Haruki (Sci Rep, 2021)
It is established that smoking is a major risk factor of atherosclerosis. Endothelial dysfunction occurs in the initial step in the pathogenesis of atherosclerosis and plays a critical role in the development of atherosclerosis. The purpose of this study was to evaluate the association between smoking status and endothelial function in detail in men. We measured flow-mediated vasodilation (FMD) in 2209 Japanese men including 1181 men who had never smoked and 1028 current smokers. All of the participants were divided into five groups by smoking pack-years: never smoker group (= 0), light smoker group (> 0 to 10), moderate smoker group (> 10 to 20), heavy smoker group (> 20 to 30) and excessive smoker group (> 30). FMD significantly decreased in relation to pack-years (6.6 ± 3.4% in the never smoker group, 6.8 ± 3.0% in the light smoker group, 6.5 ± 2.9% in the moderate smoker group, 5.9 ± 2.9% in the heavy smoker group, and 4.9 ± 2.7% in the excessive smoker group; P < 0.001). After adjustment for age (≥ 65 years), body mass index, systolic blood pressure, low-density lipoprotein cholesterol, glucose, and year of recruitment, FMD was significantly smaller in the excessive smoker group than in the never smoker group as a reference group (OR 1.95, 95% CI 1.42 to 2.67; P < 0.001). These findings suggest that FMD decreases with an increase in the number of cigarettes smoked and that excessive smoking is associated with endothelial dysfunction. Cigarette smoking is harmful to vascular function in men who are heavy smokers.